Result s of Experimental Researches of Plant Material Twin-Screw Compactor - Milko, Dmytro (University of Rousse ; Bulgarian national society of agricultural engineers "Engineering and Research for Agriculture", 2015)
The usage of latest technological means of plant material compaction will reduce production costs by saving the livestock nutrients during a storage period. The results of twin-screw compactor experimental researches are presented. They will enable to reduce production costs by saving livestock nutrients during storage. The data will provide plant material with high output density avoiding the relaxation effect. Mathematical equations of productivity, power capacity and energy intensity are given depending on the design and kinematic parameters. Surfaces of mathematical equations’ responses are also presented.
Keywords: plant materials; twin-screw compactor; haylage